Analisis Dampak Penggunaan E-Commerce dalam Meningkatkan Omzet Penjualan Usaha Mikro Kecil Menengah di Kota Makassar - Muhammad Ikhsan; Muhammad Hasan (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2020)
This study aims to determine what are the impacts of using E-Commerce in increasing MSME sales turnover. This study uses a qualitative approach that is descriptive analysis. The data collection techniques used are observation, interview and documentation techniques. The research subjects were 5 MSME actors in the city of Makassar. The results showed that there are two impacts of using E-Commerce, namely positive impacts and negative impacts. The positive impact is the use of E-Commerce, namely, the store can be accessed 24 hours, provides security and convenience in the transaction process, eases promotions so that it can help communicate faster with customers and can access the global market and can satisfy customers and of course can increase sales turnover. Meanwhile, the negative impact is that if the goods are damaged, the goods can be checked and result in losses in shipping and packing costs, the number of rivals, admin fees charged to buyers and sellers, the COD system that makes sellers feel disadvantaged because the funds are released after the goods arrive.